Field Performance and Yield of Four Pigeonpea Varieties in Middle Tennessee. (1st November 2014) - Yu, Chih-Li; Hui, Dafeng; Johnston, Trevor; Porter, Kadijah; Miller, Camerra; Duseja, Desh; Tegegne, Fisseha
Abstract : As the demand in the United States for legume crops such as pigeonpea [ Cajanus cajan (L.) Millsp.] increases, it becomes increasing important to improve yield and extend the area where pigeonpea may suitably be grown. To understand the effect of agricultural management on the leaf physiology, growth, and yield of pigeonpea, a 3‐yr (2010–2012) field experiment was conducted in Nashville, TN. A split‐split‐plot experimental design with two planting dates in years 2010 and 2012, and one late planting in 2011 were used (main plot factor, early and late planting). Four pigeonpea varieties (subplot factor, GA1, GA2, W1, and W3) at three plant densities (sub‐subplot factor, 295, 500, 145, 250, and 96, 833 plants/ha) were planted. Maximum leaf photosynthesis, stomatal conductance, transpiration, plant height, plant stem diameter, leaf area index (LAI), and seed yield were measured. There were significant differences in leaf physiology, growth and yield among varieties, between planting dates, and between years. Leaf transpiration (5.4 mmol H2 O/m 2 /s) and yield (1048 kg/ha) were higher at early planting than at late planting (4.8 mmol H2 O/m 2 /s, 2.64, and 629 kg/ha), but height (138 cm) was lower at early planting than at late planting (150 cm). Among varieties, GA2 plants were shorter (131 cm) and had lower LAI (1.61), but produced higher seed yield (1263 kg/ha). Plant density did not show significant influence on leaf physiology, LAI, or yield. All variables measured showed remarkable variation between years. Our results indicated that variety selection and early planting may improve pigeonpea growth and yield in middle Tennessee.